Post-Conflict Recovery and Peacebuilding - Hoeffler, Anke; Ijaz, Syeda Shahbano; von Billerbeck, Sarah (Washington, DC: World Bank, 2012)
Finds that civil wars, the most common type of large scale violent conflict, are long, brutal and continue to harm societies even after conclusion. Post-conflict countries face extraordinary development and security challenges as they move toward economic recovery. As most countries experience increased growth after the end of the war, external aid helps them to make the most of this peace dividend; however, aid is only growth enhancing when the violence has stopped, so in violent post-war societies aid fails to create a growth enhancing effect. Good governance is robustly correlated with growth; however, whether aid increases growth conditional on good policies is unclear. Likewise it is unclear which types of aid and policy should be prioritized. The effect of UN missions does not necessarily result in economic growth and case studies are needed for better insight into the relationship between security guarantees and economic stabilization.